Analisis perbandingan tools pengujian otomatis pada GUI aplikasi berbasis WEB - Putra, Yudha Pramana (Maliki Interdisciplinary Journal, 2024)
This research compares Selenium Webdriver and Katalon Studio in testing the graphical user interface (GUI) on the Quizizz web application. This research uses the Software Testing Life Cycle (STLC) method to compare Selenium Webdriver and Katalon Studio in testing the graphical user interface (GUI) on the Quizizz web application. The results show Selenium Webdriver is faster in test case execution and supports scrolling, but requires additional installation for image-based tests. Katalon Studio stands out for its complete documentation of execution results and support for multiple programming languages. Tool selection must be tailored to the specific testing needs of the intended application, taking into account the characteristics and capabilities of each tool to increase the efficiency and effectiveness of GUI testing.